CREATIVE MANAGEMENT AS A TOOL FOR INCREASING THE COMPETITIVENESS OF ENTERPRISES' PRODUCTS - KRAVCHYK, Yuriy; GARAFONOVA, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the course of writing this article, an in-depth analysis of the theoretical aspects of creative management as a tool for increasing the competitiveness of enterprises' products was carried out. The article is aimed at highlighting innovative approaches to management and the creative process that contribute to effective management and stimulate the development of enterprises in the current global market environment. The essence of the concepts of creativity and creative management and their impact on the quality and innovativeness of products in the market are investigated. The place and state of innovative development in the global market environment of Ukraine, including the indicator of creative results of national enterprises, are studied. The principles of creative management, which ensure the competitiveness and sustainability of enterprises in the market, are generalized. Key creative management strategies that ensure a high level of product quality are identified. It is substantiated that the intensification of creative processes solves the production and economic challenges of enterprises, facilitating their adaptation to changing market conditions and improving product quality. The article analyzes the role of consumers in shaping product quality and reveals how their requirements and choices influence the choice of a creative management strategy. It is determined that the successful implementation of creative management requires an integrated approach and active interaction of all stakeholders of the enterprise. It is established that creative management not only contributes to raising the level and standards of product quality, but is also critical for strengthening the market position of an enterprise.
Keywords: creative management; competitiveness; product quality; innovation strategies; creative processes; business management; consumers